The garden of lost secrets - Bowen, Kelly (Romance fiction writer) (Forever, 2023)
"Based upon a remarkable true story, The Garden of Lost Secrets is the riveting tale of one woman's courage and resilience and her secrets lost in the chaos of war. 1940 - Stasia always found comfort in the idyllic French countryside where she spent her childhood summers, roaming the gardens of an old chateau and finding inspiration for fairy tales full of bravery and courage. But these days are much darker, and with Nazis storming across Europe, she soon finds herself one of the most hunted agents of the Resistance. The only safe haven she can think of is Chateau de Montissaire. But she's about to discover that it just may be the center of her biggest mission yet. Present day - When Isabelle purchases a crumbling chateau in Rouen, it's not just a renovation project-it's a chance to reconnect with her sister, Emilie, the only family she has left. What she uncovers instead is an intriguing mystery... As the siblings piece together the incredible truth behind the fairy tales written by their great-grandmother Stasia, they discover an exciting tale of courage in the face of treachery and an explosive secret that will change everything they believed about their family"--